PELATIHAN TEKNIS APARATUR SIPIL NEGARA PADA BADAN PENDAPATAN DAERAH KOTA PEKNABARU - Dela Hantrini Prillia; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
There is a policy regulation from the Ministry of Finance on the management of regional tax administration which requires technical training for officers who manage regional tax administration and have differences in educational background and competence as well as changes and advances in education and information technology in managing regional tax administration. Therefore, the Pekanbaru City Regional Revenue Agency needs to hold technical training for its apparatus to support the competence of employees in managing regional tax administration. This study aims to describe the implementation of the development of the state civil apparatus through technical training and the factors that influence the implementation of technical training. The type of research used in this study is qualitative research with descriptive analysis. The informants in this study were 5 people. As for data collection techniques by means of observation, interviews and documentation. The results of this study show that the implementation of technical training held by the Pekanbaru City Bapenda is in good condition based on the theory of training indicators proposed by dessler. However, since the COVID-19 pandemic, the pekanbaru city bapenda has not carried out training due to limited apbd and does not have its own training infrastructure. Keywords: Training, Technical, Technical Training, State Civil Apparatus